Adolescents' perspectives on food literacy and its impact on their dietary behaviours. (1st December 2016) - Ronto, Rimante; Ball, Lauren; Pendergast, Donna; Harris, Neil
Abstract: Food literacy has been identified as a promising approach to support healthy dietary behaviours in adolescents. However, adolescents' perspectives on food literacy and the impact it could have on their dietary behaviours are not well understood. This study explored adolescents' perspectives on the potential for food literacy to influence their dietary behaviours. Fifteen focus groups were conducted with adolescents aged 12–17 years and encompassed quantitative and qualitative questions. Adolescents were asked to rank 22 aspects of food literacy in order of importance and discuss their responses as a group. Overall, adolescents ranked food and nutrition knowledge as more important than food skills and food capacity. Although adolescents stated that food and nutrition knowledge is important for them to eat well, the majority did not apply their knowledge to practice due to low confidence in food skills. Participants demonstrated very limited knowledge about macro aspects of food literacy such as animal welfare or environmental sustainability. Food skills such as planning and managing budgets for food and time for food shopping were ranked as least important due to being presently irrelevant but recognised as important later in life. Adolescents reported being very interested in developing food skills such as food preparation but they had very limited opportunities due to lack of food literacy education in home and high school settings. The high school setting provides an ideal opportunity for adolescents to improve their food literacy in particular food skills through home economics. Future research should develop and measure adolescents' food literacy and its impact on their dietary behaviours.